2022
DOI: 10.1186/s40494-022-00811-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined, sequential dye analysis and radiocarbon dating of single ancient textile yarns from a Nazca tunic

Abstract: The accessioning of ancient textiles into museum collections often requires objective information regarding the object’s appropriateness and authenticity before purchase or gift acceptance. In the case of colored fabrics, the identification of dyestuffs consistent with the attributed time period and culture builds confidence and reduces the chances of the object being a simple forgery or fake produced using modern materials. Moreover, this information adds to the technical, cultural, and conservation knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Among the indigo-producing plants and dyed fibers examined by Laursen and Mouri [33], those that contain pseudoindirubin include woad (Isatin tinctoria), which is commonly found and historically widely used in Europe, rattlebox (Crotalaria incana) from the West Indies, and yangua (Cybistax antisyphylitica) from South America. Indeed, the present authors confirmed the presence of pseudoindirubin 1 and 2 along with indigotin and an unusually large chromatographic peak for indirubin in black and brown yarns from a late Nazca period woolen tunic that was radiocarbon dated to between 595 and 665 CE [21], consistent with the use of indigo from yangua in Pre-Columbian textiles [50]. Moreover, Laursen and Mouri found that pseudoindirubin 1 and 2 were absent in extracts of fiber dyed by Asian indigo dye plants such as Indian indigo (Indigofera tinctoria) and the Japanese ryukyu-ai (Strobilanthes cusia) and sukuno-ai (Polygonum tinctorium).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Among the indigo-producing plants and dyed fibers examined by Laursen and Mouri [33], those that contain pseudoindirubin include woad (Isatin tinctoria), which is commonly found and historically widely used in Europe, rattlebox (Crotalaria incana) from the West Indies, and yangua (Cybistax antisyphylitica) from South America. Indeed, the present authors confirmed the presence of pseudoindirubin 1 and 2 along with indigotin and an unusually large chromatographic peak for indirubin in black and brown yarns from a late Nazca period woolen tunic that was radiocarbon dated to between 595 and 665 CE [21], consistent with the use of indigo from yangua in Pre-Columbian textiles [50]. Moreover, Laursen and Mouri found that pseudoindirubin 1 and 2 were absent in extracts of fiber dyed by Asian indigo dye plants such as Indian indigo (Indigofera tinctoria) and the Japanese ryukyu-ai (Strobilanthes cusia) and sukuno-ai (Polygonum tinctorium).…”
Section: Discussionsupporting
confidence: 80%
“…The detection of pseudoindirubins in approximately half of the blue samples from the tapestry studied here may indicate that indigo from different plant sources, probably both European woad together with Indian indigo, were used on the tapestry by the Mattens workshop. This discovery adds to the relatively sparse literature on this recently discovered, but potentially important, marker dye compound [21,33].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations